Digitalisasi Layanan Kesehatan: Pelatihan IT untuk Kader Posyandu Desa Simogirang dalam Pencatatan Data Kesehatan - Rony Kriswibowo; Rusina Widha Febriana; Johan Suryo Prayogo; Purwanto Purwanto; Selfya Ningrum; Agung Teguh Setyadi; Firdaus Kamilullah Suhada; Mohammad Alif Riskyansah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service program was implemented to strengthen the digital literacy and competencies of health cadres in Simogirang Village, Prambon Sub-district, Sidoarjo Regency, particularly in the recording and management of Posyandu (integrated health service post) data. The initiative responded to ongoing issues stemming from manual documentation methods, which were prone to human error, inefficiency, and lack of integration with regional health information systems. To address these challenges, the program delivered an IT-based training module using a combination of direct instruction, demonstrations, and hands-on simulations. The training emphasized the use of accessible and cost-effective tools such as Google Forms and Google Sheets, designed in alignment with the principles of adult learning (andragogy) and Kurt Lewin’s change management model to facilitate behavioral adaptation and technology acceptance among the participants. A total of 25 health cadres participated in the program. Pre- and post-training evaluations demonstrated significant improvement in digital skills, with 80% of participants achieving a minimum of 85% accuracy in completing digital forms and managing records. In addition, a prototype digital system based on Google Workspace was successfully piloted in two Posyandu locations. This system enhanced the timeliness, accuracy, and integration of health data reporting to local health centers (Puskesmas), offering a scalable and sustainable solution for grassroots healthcare data management. Despite the positive outcomes, the program also identified key challenges, notably limited internet infrastructure and varying levels of prior digital exposure among cadres. These findings underscore the need for continuous mentoring, support from local government stakeholders, and potential investment in digital infrastructure. Overall, the initiative contributes to Indonesia’s broader goals of digital transformation in public health, particularly at the village level.